Sheep urinary tract architecture is not affected by acute urethral obstruction - Maciel, Thiago Arcoverde; de Oliveira, Clédson Calixto; Firmino, Millena de Oliveira; do Nascimento-Hama, Lismara Castro [UNESP]; Mathias, Luis Antonio [UNESP]; Artoni, Silvana Martinez Baraldi [UNESP]; Oliveira, Daniela; Amoroso, Lizandra [UNESP] (Universidade Estadual de Londrina, 2021)
Urolithiasis affects the urinary tract of small ruminants, thereby requiring the animal to prematurely terminate breeding. Morphometric study of organs can be used as a diagnostic method. Thus, this study aimed to describe the macroscopic, histopathological, and histomorphometric changes in the urinary tract of sheep with urolithiasis. For this purpose, 14 healthy male Santa Inês sheep, approximately 90 days old, were studied and fed an experimental diet. After the development of urolithiasis, the animals were reorganized into two groups, D1 (without urolithiasis) and D2 (with urolithiasis) for comparative data analysis. Sheep were necropsied to evaluate the pathological changes, followed by macroscopic morphometric analysis, and the histopathological and histomorphometric characteristics were described. Urethral necrosis and a full urinary bladder were observed in all animals that developed the disease. The comparison between sheep with and without urolithiasis showed no significant difference (P < 0.05) in the evaluated macroscopic morphometric variables, except for the right ureter width. Regarding the histopathological evaluation, multifocal areas of mild to moderate congestion within the glomerular tufts and protein in the tubular lumen of the kidneys were observed. In the liver, mild to moderate fatty degeneration was noted in the centrolobular regions, and an ulcerated focal area in the bladder mucosa was observed in only one animal. The present study demonstrated that the formulated diet was effective in inducing clinical disease. In acute obstructive urolithiasis in sheep tissue, lesions in the liver and urinary tract were observed, although there were no significant histomorphometric changes.
A arquitetura do trato urinário de ovinos não é afetada pela obstrução uretral aguda
Keywords: Histopathology; Hydronephrosis; Morphometry; Ram; Urolith